An Evaluation of the California Injury and Illness Prevention Program - Mendeloff, John (RAND Corporation, 2012)
The Injury and Illness Prevention Program (IIPP) requirement has been the most frequently cited standard in California workplace health and safety inspections almost every year since it became effective in July 1991. This evaluation of the IIPP measures program effectiveness using information on citations for violations of the program and data on worker safety in California.